Effects of Work Environment Facilities on Employee Performance - Ghous, Mer Ghausuddin; Nizami, Hamdullah; Hamid, Hameedullah (Eximia, 2023)
This study investigates the effects of working environment on employee performance in non-governmental organizations in Nangarhar province of Afghanistan. The stratified random sampling technique is used in order to collect the data from the respondents. The simple linear regression technique is used to analyses the effects of working environment on employee performance. The sample size of the study is 120 senior, intermediate, and lower level managers working with NGOs in Nangarhar. The study found that working environment has positive significant correlations with the employee performance in NGOs sector of Nangarhar province of Afghanistan. There was a considerable positive link between employee performance and working environment (r = 0.63, P 0.05). This correlation was extremely significant. The findings further show that R2 is 0.399, which indicates that 39.9% of variation in the employee performance is being introduced by working environment. The finding further disclose the positive coefficients are assigned to the variable for the working environment. This suggests that a positive link exists between employee performance and working environment in non-governmental organizations in Nangarhar province of Afghanistan. The estimated coefficient of working environment is 0.345. This implies that as working environment rises by one unit, this would cause to rise the employee performance by 0.345 units on average by keeping all other variables constant. The constant coefficient is 0.635, which indicates that employee performance is equal to 0.635 when the working environment is equal to zero.